Hubungan Pendidikan dengan Pengetahuan Tentang IMS pada Gay, Transgender, dan LSL - Resati Nando Panonsih; Ade Utia Detty; Arif Effendi; Zulfa Yusdinar Aini (ARTERI : Jurnal Ilmu Kesehatan, 2020)
Sexually Transmitted Infection is an infection mostly transmitted through sexual contact with a partner who is already infected. This infection can be transmitted through sexual activity that involves vagina, anal, penis, and mouth. Type of STIs with the highest prevalence is syphilis that is 6,0% (range 0-36,7%) in gay and MSM and regarding more than 40% - 50% transgender’s population in the world. Gay, transgender, and MSM are high risk group of STI transmission. This is because they have different sexual life. Prevalence of STIs in gay, transgender, and MSM is still high also due to lack of knowledge about STIs. Knwoledge affected by several factors including education. Someone who has higher education will be easier to receive information so that his knowledge increase. This study objective’s was to determine the relationship between education level and knowledge level about sexually transmitted infection in gay, transgender, and MSM in Bandar Lampung 2019. Methods: This is an analytic survey research with cross sectional research design. Sampling technique is total sampling. Subjects in this research are all 35 members of Gaya Lentera Muda (Gaylam) Organization. Research instrument is using questionnaire. In this research was obtained the highest distribution of education level is middle education of 19 subjects (54,3%) and the highest distribution of knowledge level is enough knowledge of 17 subjects (48,6%). The result of spearman statistical test obtained a relationship with the result of p= 0,007 (p<0,05). There is a meaningful relationship between education level and knowledge level about sexually transmitted infection in gay, transgender, and MSM in Bandar Lampung 2019. Suggestion fot next researcher, take a larger number of samples so that the result are more representative.